2017
DOI: 10.1016/j.bbi.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Death of adrenocortical cells during murine acute T. cruzi infection is not associated with TNF-R1 signaling but mostly with the type II pathway of Fas-mediated apoptosis

Abstract: Earlier studies from our laboratory demonstrated that acute experimental Trypanosoma cruzi infection promotes an intense inflammation along with a sepsis-like dysregulated adrenal response characterized by normal levels of ACTH with raised glucocorticoid secretion. Inflammation was also known to result in adrenal cell apoptosis, which in turn may influence HPA axis uncoupling. To explore factors and pathways which may be involved in the apoptosis of adrenal cells, together with its impact on the functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
(84 reference statements)
1
2
0
Order By: Relevance
“…The Fas/FasL system plays an important role in apoptosis during the acute phase in other neurological disorders, and our findings are in agreement with previous studies ( Furuichi et al, 2012 ; Tiao et al, 2014 ; Perez et al, 2017 ; Zhao et al, 2021 ). In a mouse model of traumatic brain injury, a peak in the levels of expression of Fas was noticed in the cortex and hippocampus 24 h after the injury ( Grosjean et al, 2007 ).…”
Section: Discussionsupporting
confidence: 94%
“…The Fas/FasL system plays an important role in apoptosis during the acute phase in other neurological disorders, and our findings are in agreement with previous studies ( Furuichi et al, 2012 ; Tiao et al, 2014 ; Perez et al, 2017 ; Zhao et al, 2021 ). In a mouse model of traumatic brain injury, a peak in the levels of expression of Fas was noticed in the cortex and hippocampus 24 h after the injury ( Grosjean et al, 2007 ).…”
Section: Discussionsupporting
confidence: 94%
“…Recent studies have demonstrated the importance of the CD95/CD95L pathway to the nervous system, which is involved in the occurrence and development of a variety of neurological diseases such as AD, [38][39][40][41] but whether it is associated with neuropathic pain is not clear. The main function of CD95/CD95L is to participate in the immune response, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal glands were homogenized in 4 volumes of 300 mmol/L sucrose with 1× protease inhibitor cocktail and 1× phosphatase inhibitor cocktail (SIGMA, Saint Louis, USA). Homogenates were centrifuged at 1,000g to remove unbroken cells, nuclei, and heavy membranes, based on previous studies (35). Proteins were quantified according to Lowry technique (36).…”
Section: Immunoblot Assaysmentioning
confidence: 99%